Hypothalamic Epigenetics Driving Female Puberty - Toro, Carlos A. (J Neuroendocrinol, 2018)
Puberty involves a series of morphological, physiological and behavioral changes during the last part of the juvenile period that culminates in the attainment of fertility. The activation of the pituitary-gonadal axis by increased hypothalamic secretion of Gonadotropin Releasing Hormone (GnRH) is an essential step in the process. The current hypothesis postulates that a loss of transsynaptic inhibition together with a rise in excitatory inputs are responsible for the activation of GnRH release. Similarly, a shift in the balance in the expression of puberty activating (PA) and puberty inhibitory (PI) genes exists during the pubertal transition. In addition, recent evidence suggests that the epigenetic machinery controls this genetic balance, giving rise to the tantalizing possibility that epigenetics serves as a relay of environmental signals known for many years to modulate pubertal development. Here we review the contribution of epigenetics as a regulatory mechanism in the hypothalamic control of female puberty.